Opportunities Analysis of Indonesian Sharia Bank (BSI) Become Top 5 Bank in Indonesia Based on Asset Strength and Vision Mission - Kunaifi, Aang; Ali Sad, Achmad; Mawardi, Ahmad (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
The company's organizational goals can be achieved through several strategies used in determining competitive advantage, namely by using various strategies, namely by identifying the company's internal and external factors, including the role of the workforce or employees. In addition, it also develops product services through digitization that is more flexible and convenient for customers, such as the use of a single system, which means that now Bank Syariah Indonesia has one core banking system, one enterprise data, one bank code code 451, and one financial reporting. under the name Bank Syariah Indonesia (BSI). This study aims to measure BSI's opportunities in achieving the target of becoming the top 5 in the national banking industry. This research is a research with a qualitative descriptive approach. This research was carried out at Bank Syariah Indonesia KCP Molyosari Surabaya, the subjects of this research were the Branch Manager (BM), Micro Relationship and Manager Team Leader (MRMTL), Consumer Bussines Staff (CBS), Customer Service (CS), Branch Operation and Service Manager (BOSM). The data collection method in this study used interviews, observation, and documentation, then analyzed descriptively qualitatively. Through the findings in this study, it is hoped that the right and measurable strategy will be obtained in achieving the target of the top 5 banks in Indonesia